Impact of Frontier Development of Alveolar Bone Grafting on Orthodontic Tooth Movement - Miao, Yilan; Chang, Yu-Cheng; Tanna, Nipul; Almer, Nicolette; Chung, Chun-Hsi; Zou, Min; Zheng, Zhong; Li, Chenshuang (Frontiers in Bioengineering and Biotechnology, 2022)
Sufficient alveolar bone is a safeguard for achieving desired outcomes in orthodontic treatment. Moving a tooth into an alveolar bony defect may result in a periodontal defect or worse – tooth loss. Therefore, when facing a pathologic situation such as periodontal bone loss, alveolar clefts, long-term tooth loss, trauma, and thin phenotype, bone grafting is often necessary to augment bone for orthodontic treatment purposes. Currently, diverse bone grafts are used in clinical practice, but no single grafting material shows absolutely superior results over the others. All available materials demonstrate pros and cons, most notably donor morbidity and adverse effects on orthodontic treatment. Here, we review newly developed graft materials that are still in the pre-clinical stage, as well as new combinations of existing materials, by highlighting their effects on alveolar bone regeneration and orthodontic tooth movement. In addition, novel manufacturing techniques, such as bioprinting, will be discussed. This mini-review article will provide state-of-the-art information to assist clinicians in selecting grafting material(s) that enhance alveolar bone augmentation while avoiding unfavorable side effects during orthodontic treatment.